Organic Farming: A Vision for a Sustainable Nation - Nandini Dutta, Subhashini S (International Journal of Modern Agriculture, 2021)
Quality of the food products and their protection has become one of the significant concern that demands more attention of general public as well as of government. The people are consuming the food products that comprising of high pesticides, large amount of the nitrate, huge amount of the metals, antibiotic residue and many more that contribute to the negative health effects of conventionally produced foods. Furthermore, conventionally produced foods are lower in nutritional value and have less antioxidant. Because of the possible health benefits and food safety issues, demand for organically grown foods has risen in recent decades in the search for healthy food. Organic farming is characterized as farming without utilization of synthetic or various types of fertilizers or certain pesticides, growth hormones or antibiotics. Because of their nutritional and health advantages, organically grown up foods products are becoming more popular rapidly. Organic farming is preserving environment as well as makes a nation more healthy and prosperous. India is an indigenous country that has capacity and growth potential in organic farming. Despite being behind the curve in rapid acceptance of the organic agricultural for a number of reasons, India has experienced rapid development in the field of organic farming that has become world’s major organic producers. Thus, by ensuring sustainable growth, organic farming having countless effect on fitness of any developing country namely India.